2010
DOI: 10.1111/j.1478-3231.2010.02218.x
|View full text |Cite
|
Sign up to set email alerts
|

Maternal hepatitis B virus or hepatitis C virus carrier status as an independent risk factor for adverse perinatal outcome

Abstract: Keywords congenital malformations -hepatitis Bhepatitis C -perinatal mortality -pregnancy outcome -premature rupture of membranes -preterm delivery Correspondence

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
116
2
5

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(131 citation statements)
references
References 14 publications
8
116
2
5
Order By: Relevance
“…Likewise, our study, the only one performed in Europe in the last 20 years, shows no significantly increased prevalence of maternal and neonatal morbidity. In contrast, a very recent study from Israel showed significantly higher rates of perinatal mortality and low birth weight in newborns from HBsAg and/or anti-HCV-seropositive women [18]. In the Hong Kong study by To et al [17] with the still largest cohort studied with 1,340 HBsAg-positive women, there was even a lower risk for gestational hypertension and preeclampsia, but a higher prevalence of meconium-stained amniotic fluid which tended to be the case in our data as well.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, our study, the only one performed in Europe in the last 20 years, shows no significantly increased prevalence of maternal and neonatal morbidity. In contrast, a very recent study from Israel showed significantly higher rates of perinatal mortality and low birth weight in newborns from HBsAg and/or anti-HCV-seropositive women [18]. In the Hong Kong study by To et al [17] with the still largest cohort studied with 1,340 HBsAg-positive women, there was even a lower risk for gestational hypertension and preeclampsia, but a higher prevalence of meconium-stained amniotic fluid which tended to be the case in our data as well.…”
Section: Discussionmentioning
confidence: 99%
“…These were in concordance with studies published among other populations till date. [15][16][17] An exception is the prevalence of gestational diabetes mellitus among hepatitis carriers, which was found to be higher only in women who had an excessive weight gain during their pregnancy. The differences in BMI values may explain the diversity of the results.…”
Section: Discussionmentioning
confidence: 99%
“…47,48 HBV infection does not directly threaten maternal or fetal lives; [49][50][51][52][53][54][55] however, gestational diabetes mellitus, antepartum hemorrhage, and preterm labor have been reported in chronic carriers. [56][57][58] The most significant risk of HBV infection during pregnancy is the potential for viral transmission to the fetus or neonate, 7,[59][60][61][62] which is associated with 4.5 million cases annually. 63 More than 90% of neonates with chronic infections received hepatitis B virus from their mothers.…”
Section: 21mentioning
confidence: 99%